Narcissism, Low Self-Control, and Violence Among a Nationally Representative Sample. (June 2015) - Larson, Matthew; Vaughn, Michael G.; Salas-Wright, Christopher P.; Delisi, Matt
A growing body of evidence has highlighted the relationship between narcissism and violence. Importantly, however, the predominance of this evidence comes from experimental tests or small-scale samples that most often overlook the contribution of low self-control to explicating the relationship. The present study refers to the National Epidemiological Study of Alcohol and Related Conditions (NESARC) to assess narcissism, low self-control, and violence among a nationally representative sample. Using Latent Class Analyses (LCA), four classes of individuals are identified, and multinomial regression models indicate that narcissism and low self-control are associated with a range of violent acts among these groups. Most importantly, results show that the class of individuals that is high in narcissism and deficient in self-control is far and away the most prone to violence. Together, these findings lend important nationally representative support to recent experimental and meta-analytical conclusions suggesting that the co-occurrence of narcissism and low self-control has significant implications for our understanding of violence. Limitations of this study and avenues for future research are discussed.